Hydrogen fuel cells for road vehicles - Corbo, Pasquale; Migliardini, Fortunato; Veneri, Ottorino (Green energy and technology, 2011)
This book addresses the main issues related to the application of hydrogen fuel cell technology in the road transportation sector. Offers an introductory approach to fuel resources and atmospheric pollution concerns